On new types of rational rotation-minimizing frame space curves. (May 2016) - Cheng, Charles Ching-An; Sakkalis, Takis
Abstract: The existence of rational rotation-minimizing frames (RRMF) on polynomial space curves is characterized by the satisfaction of a certain identity among rational functions. In this note we prove that previously thought degree limitations on that condition are incorrect. In that regard, new types of RRMF curves are discovered.